System vaccinology : the history, the translational challenges and the future. - Prajapati, Vijay Kumar (Elsevier Academic Press, 2022)
Emergence of new and deadly infectious diseases is significantly deteriorating the human health. Development of vaccine by the scientist has become an important weapon to control the spread of infectious diseases as well as to improve the life expectancy at global level in 20th-21st Century. This book will provide the in-depth knowledge of vaccine history, and development of new strategies to design efficacious and safe vaccine molecule. This book will cover the development of system vaccinology and their applications revolutionize the vaccine discovery. This will provide a resource for the basic and clinical researcher working to human life expectancy by their vaccine experiments and clinical trials. My purpose to write this book to educate the students and researchers with modern development in the field of vaccinology and empowering the researcher with new tools and methodology for developing potential and immunogenic vaccines. This book will be helpful to solve the curiosity of science and medical background students related with vaccinology and will be helpful to devise a new vaccine molecule to control the spread of new and emerging pathogens. Systems biology is a rapidly expanding research discipline aiming to integrate multifaceted datasets generated using state-of-the-art high- throughput technologies such as arrays and next-generation sequencing. Combined with sophisticated computational analysis we are able to interrogate host responses to infections and vaccination on a systems level, thus generating important new hypotheses and discovering unknown associations between immunological parameters.